Formation of National Solidarity Among Senior High School Students Through Digital Technologies - Treitiak, Dmytro (Theoretical and Methodical Problems of Children and Youth Education, 2025)
This article analyzes the results of an experiment aimed at the formation of national solidarity among high school students through the use of modern digital technologies. It provides a comprehensive examination of the role of digital space in the process of building national solidarity. The study highlights the specific features of utilizing digital environments in working with high school students, emphasizing their potential as educational tools. The author substantiates and describes effective methodologies for cultivating national solidarity among youth via digital means, identifying the most impactful approaches. The main outcomes of the experiment are presented, along with an overview of the most effective engagement strategies for young people. The reasons for the success of the selected methods are also discussed. The article outlines the significant potential of digital space as a communicative platform for fostering personal interaction between teachers and students. Additionally, it explores how traditional educational forms and methods can be adapted to the contemporary realities of a digitized educational environment. It demonstrates how these practices can be effectively transferred to digital platforms while maintaining their efficacy, thereby enhancing the overall impact of educational processes under modern conditions. Based on the conducted analysis, practical recommendations are offered for implementing digital tools to strengthen national solidarity among youth. The study also identifies the most user-friendly and accessible digital platforms for working with students and outlines their application in educational contexts. The practical significance of this study lies in its potential use by educators, researchers, youth policy specialists, and students involved in organizing educational activities in general, special, vocational, and technical education institutions. It also contributes to national-patriotic education within the digital space, particularly in fostering national solidarity among high school students.